Asupan Makan Sehari, Status Gizi, dan Produktivitas Kerja Guru SMK Pelita Ciampea Bogor - Fadilatunnisa Hayatunnufus; Vitria Melani; Putri Ronitawati; Prita Dhiyani Swamilaksita (Jurnal Kesehatan Indonesia, 2022)
Teachers are one of the key factors determining the quality of education. Teacher’s work productivity might be influenced by their daily food intake and nutritional status. The objective of this study is to determine the relationship between daily food intake and nutritional status to the work productivity of teachers. This research used a cross-sectional approach that was carried out at SMK Pelita Ciampea Bogor. The research samples were 75 teachers selected by simple random sampling method. Characteristic data was obtained through interviews and filling out questionnaires. The instruments used to measure nutritional status were digital scales and microtoise. The daily food intake data were obtained from the interview results using the 1x24 hour food recall form. Work productivity data was obtained by filling out a questionnaire containing 25 closed questions. The data were analyzed using the chi-square test. The results showed that teacher's food intake was lower than their recommended dietary allowance. Most of the teachers were obese but had very good work productivity. Bivariate analysis showed that there was no significant relationship between nutritional intake and work productivity (p>0,05). In daily food intake, only fat intake had a significant relationship to work productivity (p=0,004). It could be concluded that fat intake had a significant relation to work productivity.